Edukasi tentang Protokol Pencegahan Covid-19 kepada Masyarakat Kelurahan Lebak Bandung Kota Jambi - Fithriyani Fithriyani; Marnila Yesni (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
The number of Covid 19 cases is increasing and cannot be ignored considering the increase every day continues to increase. The impact of the Covid 19 pandemic has an impact on various fields, especially the economy. To avoid the increasing number of sufferers, the government limits activities that cause crowds, maintains distance and maintains hygenicity in the community in carrying out daily activities known as health protocol regulations. The behavior and actions of the community must change completely from the usual actions that are often carried out, for that it is necessary to have socialization on how to prevent the transmission of Covid 19 by implementing the health protocol that has been advised by the government. The purpose of this community service activity is to remind and help public understanding of the implementation of health protocols during the Covid 19 pandemic. The form of activities is in the form of counseling, giving hand sanitizers and masks. Lack of public awareness and knowledge about Covid-19 can be overcome by providing knowledge, through socialization about the importance of implementing this activity protocol in order to help people face New normal conditions, by helping people live by complying with health protocols. The results of the activity obtained the enthusiasm of the residents in following the activity until the end with the many questions asked. Suggestions for the Lebak Bandung Village to hold outreach activities about the prevention of Covid 19 in their environment because there are still many residents who do not understand about prevention which is only done